Physicochemical Characteristics of Black Bean Protein Concentrate Based on the Variation of Heating Time - Syane Palijama; Priscillia Picauly; Windarti Windarti (Tropical Small Island Agriculture Management, 2021)
One type of beans that can be used as a source of protein is the black bean (Phaseolus vulgaris. L); because it has a sufficiently high protein content of 16.6%, it has the potential to be developed into protein concentrate. This study aimed to characterize the physicochemical characteristics of black bean protein concentrate based on heating time. An experiment was carried out and arranged in a Completely Randomized Design, with four levels of treatments, i.e. heating time of 15 minutes, 30 minutes, 45 minutes, and 60 minutes. The observed variables were yield, bulk density, water absorption, protein content, moisture content, and ash content. The results showed that the yield value was 7.66 - 12.11%, bulk density 0.78 - 0.81 g/mL, water absorption 1.84 - 1.97%, protein content 71.39 - 76.00%, moisture content 11.85 - 12.94% and ash content 3.30 - 3.57%.